2009
DOI: 10.1186/1471-2490-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraprostatic Botulinum Toxin Type A injection in patients with benign prostatic enlargement: duration of the effect of a single treatment

Abstract: BackgroundBotulinum Toxin Type-A (BoNT/A) intraprostatic injection can induce prostatic involution and improve LUTS and urinary flow in patients with Benign Prostatic Enlargement (BPE). However, the duration of these effects is unknown. The objective of this work was to determine the duration of prostate volume reduction after one single intraprostatic injection of 200U of Botulinum Toxin Type-A.MethodsThis is an extension of a 6 month study in which 21 frail elderly patients with refractory urinary retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 22 publications
3
35
0
2
Order By: Relevance
“…Although prostate volume initially decreased (during the first 6 months), slowly increased soon after. On the contrary, Qmax, International Prostate Symptoms Score (IPSS), and PVR remained unchanged during the follow-up period of 18 months [66,71,72].…”
Section: Bont-a Effects In Human Prostatementioning
confidence: 67%
See 1 more Smart Citation
“…Although prostate volume initially decreased (during the first 6 months), slowly increased soon after. On the contrary, Qmax, International Prostate Symptoms Score (IPSS), and PVR remained unchanged during the follow-up period of 18 months [66,71,72].…”
Section: Bont-a Effects In Human Prostatementioning
confidence: 67%
“…A symptomatic improvement has been observed in BoNTtreated patients [2,4,65,67,81,82,[85][86][87][88]. BoNT benefit was evident within one month after the treatment, and it continued throughout the follow up period [65,66,71,72]. A decrease of AUA symptoms score and improvement of peak urinary-flow rate have been observed after BoNT injections [89,90].…”
Section: Discussionmentioning
confidence: 92%
“…BoNT-A injection in smaller prostate glands caused a much lesser reduction in prostate volume, but a 15% reduction was still observed [32,36]. Independent of the extent of prostate volume reduction, improvements in LUTS and flow have been consistently reported [29][30][31][32][44][45][46][47][48][49][50][51][52][53], while a decrease in total serum PSA was observed in some studies [e.g. 30,45,51], but not in others [52].…”
Section: Botulinum Toxinmentioning
confidence: 90%
“…However, the studies have shown no consistency in clinical response in terms of outcome parameters such as symptom scores (for example, the American Urological Association Symptom Index [AUASI] and the International Prostate Symptom Score [IPSS]), reduction in prostate volume, postvoid residual urine volume, peak urinary flow rate (Q max ) and PSA (Table 1). [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] One intriguing finding is the observation that, even without a relevant impact on prostate volume in selected patients, the application of BoNT-A resulted in an increase in peak urinary flow rate and amelioration of LUTS. 65 This observation highlights the various pathophysiological aspects underlying LUTS suggestive of BPH.…”
Section: Mechanism Of Actionmentioning
confidence: 99%